Mitochondrial dynamics and colorectal cancer biology: mechanisms and potential targets - Zihong Wu; Chong Xiao; Jing Long; Wenbo Huang; Fengming You; Xueke Li (Cell Communication and Signaling, 2024)
Abstract Colorectal cancer (CRC) is a significant public health concern, and its development is associated with mitochondrial dysfunction. Mitochondria can adapt to the high metabolic demands of cancer cells owing to their plasticity and dynamic nature. The fusion–fission dynamics of mitochondria play a crucial role in signal transduction and metabolic functions of CRC cells. Enhanced mitochondrial fission promotes the metabolic reprogramming of CRC cells, leading to cell proliferation, metastasis, and chemoresistance. Excessive fission can also trigger mitochondria-mediated apoptosis. In contrast, excessive mitochondrial fusion leads to adenosine triphosphate (ATP) overproduction and abnormal tumor proliferation, whereas moderate fusion protects intestinal epithelial cells from oxidative stress-induced mitochondrial damage, thus preventing colitis-associated cancer (CAC). Therefore, an imbalance in mitochondrial dynamics can either promote or inhibit CRC progression. This review provides an overview of the mechanism underlying mitochondrial fusion–fission dynamics and their impact on CRC biology. This revealed the dual role of mitochondrial fusion–fission dynamics in CRC development and identified potential drug targets. Additionally, this study partially explored mitochondrial dynamics in immune and vascular endothelial cells in the tumor microenvironment, suggesting promising prospects for targeting key fusion/fission effector proteins against CRC. Graphical Abstract